Investigating Shear Force and Torque of Grapevine Shoots Based on Experimental and Simulation Analysis - Lingxin Bu; Qiangqiang Zhang; Qianwen Kou; Yun Chen; Xingjia Li; Xingtao Wu; Teng Zhang; Xingrun Tang; Jipeng Wang; Li Zhao (BioResources)
Winter pruning of grapevine branches is essential vineyard management, and knowledge of the biomechanical properties of branches is crucial for effective pruning. This study analyzed the dynamic behavior of grapevine shoots through axial–radial tensile, three-point bending, and shear tests. The axial elastic modulus, the radial elastic modulus, and the flexural modulus of grapevine shoots were 797 MPa, 79.8 MPa, and 5890 MPa, respectively. A finite element model of the grapevine shoot was established using the measured data, and a three-point bending simulation was conducted. The flexural modulus value obtained from the simulation was 5700 MPa, with a deviation of 3.37% from the experimental average, demonstrating the model’s accuracy. Moreover, a mathematical regression model was developed to describe the relationship of the branch diameter with its maximum shear force and shear torque. Shear test simulations revealed the stress distribution during the shear process, with the maximum shear force and torque deviating 9.60% and 12.11%, respectively, from the experimental averages. This study provides data support for grapevine pruning automation. In the future, these findings may contribute to the development of automated mechanical pruning equipment for grapevines.